Pengaruh Motivasi Kerja, Kepuasan Kerja dan Budaya Organisasi terhadap Kinerja Karyawan - Budianto, Roma; Sudarman, La (Politeknik Baubau, 2024)
Human resources are an important pillar for a company because their quality will have an impact on the efficiency and effectiveness of its operations. The quality of human resources can be measured in several ways, such as work motivation, job satisfaction, and organizational culture. If these three variables are owned by workers, then the performance of the organization's employees can be classified as good. The purpose of this research is to determine the influence of work motivation, job satisfaction, and organizational culture on employee performance at PT. Triatra Sinergia Pratama Site Batu Kajang. The data collection technique used a purposive sampling technique where 70 employees were selected as research samples and data was collected using a questionnaire via Google Form. The data analysis technique used is multiple linear analysis with the help of SPSS IBM 25.0 software. The research results show that the variables of work motivation, job satisfaction, and organizational culture partially and simultaneously have a positive influence on employee performance. The results of this research found that to improve employee performance, companies need to provide work motivation, job satisfaction and implement a good organizational culture towards their employees.